Penilaian dan Pengembangan Potensi Objek dan Daya Tarik Wisata Alam di Taman Wisata Alam (TWA) Sibolangit (Assessment and Development of Object Potency and Pull Factor of Ecotourism at Sibolangit Recreational Park) - Irena Astria Ginting; Pindi Patana; Rahmawaty Rahmawaty (Program studi Kehutanan USU, 2013)
Sibolangit Recreational Park is an areal that has many tourism potency so that suitable as an ecotourism destination, in spite of actually this location is rarely visited of tourist. The purpose of this research is to estimate tourism potency which there are over there and to find the strategy could be done related to its development. The estimation of ecotourism in this place used guidance of ADO-ODTWA by Dirjen PHKA 2003 that had been modified. Development strategy was got by identification of strength, weakness, opportunity, and threatment at ecotourism area and then analyzed by using SWOT matriks. Result of this research showed that Sibolangit Recreational Park has ecotourism potency proper to develop with properness 69,23 % and present in the first quadran SWOT analyze. It means that Sibolangit Recreational Park exist in favorable condition because of having internal strength and external opportunity. Keywords: Ecotourism valuation and development, tourism pull factor, Tourism Potency, Sibolangit Recreational Park